DIGITAL TRANSFORMATION, MARKETING, BUSINESS SIZE, FINANCIAL LITERATION ON SMES’ COMPETITIVE ADVANTAGE - Ernestivita, Gesty; Subagyo, Subagyo (TRIKONOMIKA, 2023)
This study investigates the influence of digital transformation, marketing strategies, and business size on competitive advantage and performance in Indonesian SMEs. With a sample of 100 SMEs, the research reveals that digital transformation alone does not directly impact competitive advantage or performance. However, when mediated by financial literacy, digital transformation becomes a significant factor affecting both competitive advantage and company performance. Marketing strategies directly influence competitive advantage but not firm performance. Business size has a direct impact on both competitive advantage and performance. Financial literacy plays a crucial moderating role in shaping the relationships between digital transformation, competitive advantage, and firm performance. The findings suggest potential avenues for future research, emphasizing the need for broader sample sizes and additional variables to enhance the understanding of these dynamics in similar contexts.